THE EFFECT OF INSTAGRAM CONTENT TOWARDS INTENTION TO VISIT UC_IBMRC WITH ONLINE ENGAGEMENT AS MEDIATING VARIABLE (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Social media is an online media that is now very developed in the world of communication and business. Instagram is one of the social media that is widely used by people to get information or run a business. In this study, researchers wanted to see the effect of Instagram content on interest in visiting with online engagement as a mediating variable. This research was conducted quantitatively with structural equation modeling where the researcher had an initial research model. After testing the validity and reliability, the researcher has a final research model. The respondents in this study were 96 UC_IBMRC Instagram followers. The results of this study indicate that Instagram content has an effect on visiting interest. Instagram content affects online engagement. Online engagement has an effect on interest in visiting and at the same time becomes a variable that partially mediates the relationship between Instagram content and interest in visiting. Keywords: Instagram Content, Visiting Interests, Online Engagement